Profil Unsur Tanah Jarang Granitoid Klabat di Pulau Bangka dengan Analisis Aktivasi Neutron - Widana, Kurnia Setiawan; Priadi, Bambang; Handayani, Yustina Tri (EKSPLORIUM, 2014)
Neutron Activation Analysis (NAA) is a powerful geochemical analysis with advantages which are nondestructive and involves multi-elements. NAA technique applied for qualitative and quantitative analyses on Klabat granitic rocks that distributes and compose the geology of Bangka Island. There are 27 samples analyzed which aims to determine the content of rare earth elements, which will be applied in petrotectonic of Klabat granitoid. Rare Earth Elements (REE) which analyzed, namely La, Ce, Nd, Sm, E, Gd, Tb, Yb, and Lu. All of the samples irradiated in the Centre of Multipurpose Reactor "Siwabessy", BATAN - Serpong and subsequently counted with High Purity Germanium detector (HPGe) considering half-life and elements contents that will be concerned both qualitative and quantitative analysis. The comparative quantitative analysis method conducted using Standard Reference Material (SRM) 2710a and 2711a that published by the National Institute of Standards & Technology (NIST). The result are the pattern of spider diagram with the chondrite normalized and showing the enrichment of La-Sm as light REE (LREE) and Eu-Lu slight decreasing as heavy REE (HREE), as identify of plutonic rocks thar formed in the continental arc.